PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN - Lestari, Keukeu Firda; Tanuatmodjo, Heraeni; Mayasari, Mayasari (Business Education Program of Universitas Pendidikan Indonesia, 2017)
The problem of this research was about decrease in dividend policy BUSN Devisa listed on theIndonesia Stock Exchange which is measured by Dividend Payout Ratio (DPR) over the last twoyears. These factors affecting the dividend policy were liquidity which is measured by Loan toDeposit Ratio (LDR) and profitability which is measured by Return On Equity (ROE). Thepurposes of this study were describing the liquidity, profitability, dividend policy, the effectliquidity on dividend policy, the effect profitability on dividend policy, and the effect of liquidityand profitability on dividend policy. This research utilised descriptive and verificative, thetechnique which is used was multiple correlation, and hypothesis testing used t Test (partialsignificance test) and F Test (simultaneous significance test). The data is gained from secondarydata which is from the annual report and summary of performance BUSN Devisa from 2010-2014.The population of this study was 25 BUSN Devisa listed on the Indonesia Stock Exchange with 4samples through purposive sampling technique. The result of hypothesis testing in partial showedthat liquidity and profitability effected the dividend policy significantly. The result of hypothesistesting showed that the liquidity and profitability effected on dividend policy significantsimultaneously.